Realities and Opportunities for Islamic Education Development in Viet Nam - Cham Is Na Uy; Gusmaneli (QAZI: Journal of Islamic Studies, 2025)
Islamic education in Vietnam exists in an informal and community-based system, primarily sustained by the Cham Muslim minority. Despite the absence of a formal educational infrastructure, this system plays a vital role in preserving religious identity and transmitting moral values. This study aims to analyze the current condition of Islamic education in Vietnam, identify existing challenges, and explore development opportunities that support sustainability and cultural relevance. A descriptive qualitative approach was employed, using literature reviews and document analysis to explore educational practices, institutional gaps, and policy dynamics that shape the Islamic education landscape in Vietnam. The findings show that Islamic education in Vietnam is adaptive and resilient but suffers from limitations in curriculum standardization, educator training, and formal recognition. However, digital technology, international partnerships, and emerging government support provide promising opportunities for its development. A multi-stakeholder and culturally grounded approach is needed to strengthen Islamic education in minority contexts. This study provides practical insights for policymakers and educators in designing inclusive and sustainable educational strategies for Muslim communities in non-Muslim-majority countries